A Lifetime of Research in Creep, Superplasticity, and Ultrafine‐Grained Materials. Issue 1 (23rd August 2019) - Langdon, Terence G.
Abstract : A long‐term career at the University of Southern California, followed by an appointment at the University of Southampton, provided an opportunity to conduct extensive research into the flow behavior of polycrystalline metals. Initially, research is conducted on creep properties at elevated temperatures and it is shown that solid solution metallic alloys exhibit transitions in creep behavior with dislocation climb and viscous glide as the dominant rate‐controlling mechanisms. There are transitions between climb and glide with increasing stress and also a breakaway from the glide process at high stresses. These transitions are predicted theoretically and the results are in excellent agreement with the experimental data for a wide range of alloys. Attention is directed to the process of superplasticity and it is shown that the flow occurs by grain boundary sliding with accommodation by a limited amount of intragranular slip. Separate rate equations are developed for sliding in coarse‐grained materials and in superplastic materials where the grain sizes are generally <10 μm so that flow occurs without the development of any subgrains. Finally, attention is directed to the properties of ultrafine‐grained materials having submicrometer or nanometer grain sizes produced through the application of severe plastic deformation. Abstract : Metals deform plastically in creep when they are subjected to stresses which are lower than those required for fracture. The flow behavior in creep can be modeled to give information on the nature of the deformation mechanisms. Superplastic flow is an example of creep which can be modeled in a similar way.